Taxation and Decentralization - Bird, Richard (World Bank, Washington, DC, 2012)
Strengthening sub-national governments is high on the policy agenda of many developing countries. From an economics perspective, the most important potential benefit from decentralization is the increased efficiency (and consequent welfare gain) that comes from moving governance closer to the people. To achieve this benefit, however, close attention must be paid to the design and implementation of sub-national tax systems.